2012
DOI: 10.2527/jas.2012-4444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weaning and an antioxidant blend on intestinal barrier function and antioxidant status in pigs

Abstract: The objective of this experiment was to investigate the influence of weaning stress and an antioxidant blend on gut health and free radical metabolism in postweaning pigs. A total of 96 pigs from 12 litters were randomly divided by litter to 3 groups with 4 litters each. The control group and the weaning group were fed the basal diet, and the antioxidant group was fed the basal diet supplemented with an antioxidant blend. The control group was suckling normally during the experimental period and the other 2 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
121
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 36 publications
11
121
0
11
Order By: Relevance
“…Recent studies have indicated that early weaning may induce intestinal oxidative stress, which contributes to intestinal dysfunction (Wang et al, 2008;Zhu et al, 2012). In this study, we have investigated whether supplementing a carvacrol-thymol blend in the diet lowered early All results are presented as mean ± SEM (n = 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that early weaning may induce intestinal oxidative stress, which contributes to intestinal dysfunction (Wang et al, 2008;Zhu et al, 2012). In this study, we have investigated whether supplementing a carvacrol-thymol blend in the diet lowered early All results are presented as mean ± SEM (n = 6).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that dysfunction of the intestine, which has important immunological, metabolic and barrier functions, has been demonstrated to play a crucial role in weaning-induced growth check (Wijtten et al, 2011;Campbell et al, 2013). Recent studies have indicated that decreased antioxidant activity and increased production of reactive oxygen species (ROS) is involved in weaning-induced intestinal dysfunction, resulting in intestinal oxidative stress (Wang et al, 2008;Degroote et al, 2012;Zhu et al, 2012). The intestinal oxidative stress is frequently associated with inflammation (Rada et al, 2011;Padgett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria Spirulina platensis and freshwater microalga Chlorella vulgaris are frequently referenced in human nutrition for their physicochemical properties with a potential benefit on gut health, such as antioxidant, anti-inflammatory and antimicrobial activities (Kitada et al, 2009;Hoseini et al, 2013). In pigs, Spirulina and Chlorella could help maintaining digestive function after weaning by limiting intestinal damage caused by immune and inflammatory responses to dietary transition and oxidative stress Zhu et al, 2012). Dietary supplementation with Spirulina and Chlorella has been considered for their nutritional value (Lipstein and Hurwitz, 1980;Yap et al, 1982), but few studies considered Spirulina and Chlorella as functional ingredients (Janczyk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with control pigs, the total tract energy digestibility was greater in pigs receiving diets supplemented with Spirulina or Chlorella and the digestibility tended to be greater for DM, organic matter and NDF. The dietary transition at weaning involves an intestinal release of free radicals responsible for oxidative stress (Zhu et al, 2012) Furbeyre, van Milgen, Mener, Gloaguen and Labussière and an increased expression of pro-inflammatory cytokines . These cytokines are supposed to be responsible for the alteration in mucosal structure (Pluske et al, 1997), with a drastic decrease in villus height and brush border enzyme activities during the first 5 days after weaning (Pluske et al, 1997;Lallès et al, 2004), reducing nutrient absorption and growth performance .…”
mentioning
confidence: 99%
See 1 more Smart Citation